2022
DOI: 10.1155/2022/5467498
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Neuroprotective Effects of Sarcosine

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by behavioral and psychological symptoms in addition to cognitive impairment and loss of memory. The exact pathogenesis and genetic background of AD are unclear and there remains no effective treatment option. Sarcosine, an n-methyl derivative of glycine, showed a promising therapeutic strategy for some cognitive disorders. To our knowledge, the impacts of sarcosine supplementation against AD have not yet been elucidated. Therefore, we aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 77 publications
2
7
0
Order By: Relevance
“…Profiling of mango kernels revealed for 5 major amino acids and nitrogenous compounds exemplified by sarcosine, ethyl ester, nicotinic acid and L-threonine, with sarcosine-methyl ester as major components ranging from 3.3 to 4.7 µg/mg. Sarcosine is recently recognized for its CNS effects against depression, anti-inflammation in the brain 45 , in addition for management of schizophrenia and Alzheimer’s disease 46 , 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Profiling of mango kernels revealed for 5 major amino acids and nitrogenous compounds exemplified by sarcosine, ethyl ester, nicotinic acid and L-threonine, with sarcosine-methyl ester as major components ranging from 3.3 to 4.7 µg/mg. Sarcosine is recently recognized for its CNS effects against depression, anti-inflammation in the brain 45 , in addition for management of schizophrenia and Alzheimer’s disease 46 , 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Sarcosine is also responsible for enhancing the function of the N ‐methyl‐ d ‐aspartate receptor [35]. Previous studies have shown that sarcosine has a neuroprotective effect as it is effective in reducing oxidative stress [36]. These findings could justify the increase in sarcosine levels in response to cortisol during GR and MR activation and their cooperation with each other.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, sarcosine is a glycine transporter type-I inhibitor and NMDAR allosteric modulator, directly binding to the NMDAR glycine co-agonist site, enhancing NMDAR activity, and possessing neuroprotective properties 91 , 92 . However, previous studies (not included in our study due to our exclusion criteria) suggested that sarcosine may not be effective when used as an augmentation agent with clozapine.…”
Section: Discussionmentioning
confidence: 99%